Characterization of a Lymphoid Organ Specific Anti-lipopolysaccharide Factor From Shrimp Reveals Structure-Activity Relationship of the LPS-Binding Domain - Li, Shihao; Lv, Xinjia; Li, Fuhua; Xiang, Jianhai (Frontiers in Immunology, 2019)
Anti-lipopolysaccharide factor (ALF) is a kind of important antimicrobial peptides with broad-spectrum antimicrobial activities. The LPS-binding domain (LBD) contributes to the major antimicrobial activity of ALF. However, LBDs from different ALFs share low sequence similarity. The general character of LBDs needs to be elucidated to understand the molecular mechanism of their function and facilitate LBD-original drug design. Here we identified a lymphoid organ specifically expressed ALF, designated as FcALF8, from the Chinese shrimp Fenneropenaeus chinensis. The synthetic LBD peptide of FcALF8 (LBD8) showed strong antibacterial activities to the pathogenic Vibrio, such as Vibrio alginolyticus, Vibrio harveyi, and Photobacterium damselae with a MIC value of 0.5-1 μM, 1-2 μM and 1-2 μM, respectively. FcALF8 knock-down using dsRNA led to significant increase of the viable bacteria in the lymphoid organ and hepatopancreas of shrimp upon V. harveyi infection. On the contrary, the proliferation of V. harveyi in the shrimp lymphoid organ and hepatopancreas significantly decreased after infected by LBD8 pre-incubated V. harveyi. Sequence alignments showed that the LBDs from 39 ALFs shared only two identical cysteine residues. However, 17 of the total 22 LBD residues showed high similarity when the amino acids were classified into hydrophobic and hydrophilic ones. A further activity analysis on modified LBD8 peptides showed that the antibacterial activity of LBD8 was lost after linearization and apparently weakened after changing the amino acid property at certain positions. The data indicated that the disulfide bond and amino acid property contributed to the conservation of the functional domain. To the best of our knowledge, this is the first identified ALFs specifically expressed in the lymphoid organ of shrimp with strong antibacterial activity. The present data will give creative instructions for the design of LBD-originated antimicrobial agents.